Closed loop controlled boost converter using a pid controller for solar wind power system installation - Sharma, Prakhar; Kumar, Pankaj; Sharma, Himanshu; Pal, Nitai (International Journal of Engineering and Technology, 2018)
Deployment of renewable energy resources on distributed energy system has reduced the reliance and transmission losses from the utility grid. It also helps to improve the system stability near the load center. Solar and wind are the two highly utilized green energy resources in present scenario. However, the fluctuations of solar irradiation, temperature, wind velocity are the preeminent issue for this type of systems which affects the efficiencyÂ  of the solar and wind energy system. It requires the interfacing unit to stabilize the output voltage. The proposed work deals with the close loop boost converter with PID controller, which is used to attain a stabilized voltage despite of parameter changes and load disturbances. Designed system will help to analyze the better stable output voltage with efficient system having minimum fluctuation.